2013
DOI: 10.1038/onc.2012.634
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel ROCK inhibitors with anti-migratory and anti-invasive activities

Abstract: ROCK1 and ROCK2 mediate important processes such as cell migration, invasion and metastasis; making them good targets for the development of antitumor agents. Recently, using a fragment-based approach and X-ray crystallography, we reported on the design and synthesis of novel Rho-kinase inhibitors (RKIs). Here, we selected a pair of RKIs, the closely-related structural analogues RKI-18 (potent; IC50 values of 397 nM (ROCK1) and 349 nM (ROCK2)) and RKI-11 (weak/inactive; IC50 values of 38 µM (ROCK1) and 45 µM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 32 publications
2
49
0
1
Order By: Relevance
“…Fasudil has been shown to inhibit tumor progression in vivo ; moreover, this inhibitor has been tested extensively in humans for the treatment of cerebral vasospasm. The recently discovered ROCKI/II inhibitors, RKI-18 and RKI-1447 have been shown to prevent migration, invasion and anchorage-independent growth of human breast cancer cells (61, 62). Further, RKI-1447 also demonstrated antitumor activities in transgenic mouse model of breast cancer, reducing mammary tumor growth by 87% (61).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Fasudil has been shown to inhibit tumor progression in vivo ; moreover, this inhibitor has been tested extensively in humans for the treatment of cerebral vasospasm. The recently discovered ROCKI/II inhibitors, RKI-18 and RKI-1447 have been shown to prevent migration, invasion and anchorage-independent growth of human breast cancer cells (61, 62). Further, RKI-1447 also demonstrated antitumor activities in transgenic mouse model of breast cancer, reducing mammary tumor growth by 87% (61).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Several studies described the inhibitory effects of ROCK blockers on in vitro adherent tumor cell migration and invasion (Gutjahr et al, 2005;Torka et al, 2006;Patel et al, 2014), although recent data showed that ROCK inhibition increases the metastatic potential of nonadherent breast tumor cells by increasing their reattachment efficacy (Bhandary et al, 2015). ROCKs have been implicated in the pathogenesis of cancer and several aspects of human tumor progression (Rath and Olson, 2012).…”
Section: Cancermentioning
confidence: 99%
“…Consequently, they fail to block cell migration completely. Recent studies reported the development of several new ROCK inhibitors, including, OXA-06 and RKI-18, which showed good potency against ROCK in vitro and in cells (14,15). However, the OXA-06 compound has poor pharmacokinetic properties for use in vivo (14) and no in vivo data for RKI-18 were reported (15).…”
Section: Introductionmentioning
confidence: 99%